TINJAUAN KEINGINTAHUAN SEBAGAI PENDORONG MAHASISWA UNTUK MENGIKUTI PROGRAM MAGANG DAN STUDI INDEPENDEN BERSERTIFIKAT MELALUI VARIABEL SOFTSKILL - Noval Vernando; Rizky Ema Wulansari; Primawati Primawati; Febri Prasetya (Unversitas Negeri Padang, 2024)
Higher education in Indonesia plays an important role in developing and enhancing students' knowledge, skills, and understanding across various fields of study, in accordance with the Republic of Indonesia Law Number 12 of 2012 on Higher Education. The